INSENTIF PAJAK DAN SEKTOR PARIWISATA SELAMA PANDEMI COVID-19 DI INDONESIA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2023)
This study aims to evaluate the implementation of tax incentives from the Government of Indonesia in the tourism sector during the COVID-19 pandemic. We use a case study approach and document analysis to obtain data related to the effect of tax incentives on the tourism sector's performance. We also use data on the economic performance of the Province of Bali as a benchmark in measuring the effectiveness of tax incentives in the tourism sector. The results of this study indicate that tax incentives during the COVID-19 pandemic have not provided maximum support for the tourism sector. The weak impact of tax incentives in the tourism sector is due to the sharp economic decline in the tourism sector and the design of tax incentives that have not yet touched local taxes as the domain of taxes in the tourism sector. Thus, the government needs to consider providing tax incentives that are not limited to central taxes, but also regional taxes. Keywords: Tax Incentives, Tourism Sector, COVID-19 Pandemic